Evaluating the Efficiency of Intensive Care Unit Departments in Hospitals Affiliated with Yazd University of Medical Sciences Using Data Envelopment Analysis - Mahdieh Abedi (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2017)
Background: Despite the resources allocated to hospitals, there is a gap between resources at hand and those needed in hospitals. This study aimed to evaluate the efficiency of intensive care unit departments of hospitals affiliated with Yazd University of medical sciences in 2012. Methods: This descriptive, analytical, cross-sectional, and retrospective study employed data envelope analysis (DEA) to examine efficiency in a sample of ICU departments in 7 selected hospitals. In this study, input variables included the number of physicians, nurses, beds, and medical equipment (Ventilators), while the output variables consisted of the number of discharged healthy patients, bed occupancy rate, economical information such as bed price, as well as physicians and nurses' fees.  Data were collected through the study of documents, then, they were imported into the DEAP 2.1 software and various efficiencies were calculated. Results: The efficiency means of scale, managerial, technical, allocative, and economic calculated for ICU wards were respectively about 0.991, 0.890, 0.883, 0.956, and 0.866 in 2012. Conclusion: Excess human and capital resources costs are a heavy burden for hospitals to bear and surplus production factors paly a substantial role in decreasing hospitals’ costs. So, intensive care units with efficiencies of less than 1 are recommended to decrease their excess resources to achieve the optimal efficiency.